Process simulation on the planning of wind-PV storage for near-zero carbon emission - Linna, Hou; Yi, Bai; Juning, Su (Frontiers in Energy Research, 2023)
The proposal of the dual carbon policy has put forward new requirements for the planning of wind power photovoltaic energy storage, which should not only meet economic requirements but also consider the timeliness of carbon reduction. Particularly, in recent years, there has been a contradiction between energy waste and power shortage in some regions of China, which needs to be resolved through reasonable planning of the capacity of multi energy systems. Based on the aforementioned background, this paper uses system dynamics simulation to analyze the efforts that should be made to maintain a stable energy balance between wind–solar power generation output and energy storage capacity when considering the cost of the power side and the demand response level of the load side. We assume a development plan for wind and solar energy, and optimize the allocation of energy storage capacity under these conditions to meet the balance requirements of carbon reduction and investment cost reduction. We use system dynamics simulation to simulate the energy storage demand under the demand response. In order to achieve the near-zero carbon goal, this paper discusses the reasonable state of a power energy structure based on different carbon emission reduction goals. Finally, we discovered the relationship between investment costs and carbon reduction targets as increasing carbon reduction targets will greatly increase investment costs and provide some suggestions for planning.